The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/mame.201200111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maleic‐Anhydride Grafting on the Physical and Mechanical Properties of Poly(L‐lactic acid)/Starch Blends

Abstract: MA is grafted onto both PLLA and starch in an internal mixer in the presence of DCP in a one‐step reactive compatibilization process. The effect of maleation of MA on the physical and mechanical properties and morphology of the blends was assessed. The onset decomposition temperature of the PLLA/starch blends decreased as the starch content increases due to the lower thermal stability of starch and the low effect of the maleation reaction on the thermal stability of the blends. PLLA/starch blends without graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 40 publications
6
48
0
Order By: Relevance
“…As presented above, using of maleic anhydride is a simple and effective way to enhance performance properties of PLA/starch blends. Similar observations have been also reported in works [112,113]. Furthermore, Świerz-Motysia et al [114] showed that biodegradation rate of PLA/TPS blends decreases with an increased content of PLA-g-MA as compatibilizer, which can be associated with its influence on the degree of crystallinity in studied blends.…”
Section: Aliphatic Polyesters/starch Blendssupporting
confidence: 86%
“…As presented above, using of maleic anhydride is a simple and effective way to enhance performance properties of PLA/starch blends. Similar observations have been also reported in works [112,113]. Furthermore, Świerz-Motysia et al [114] showed that biodegradation rate of PLA/TPS blends decreases with an increased content of PLA-g-MA as compatibilizer, which can be associated with its influence on the degree of crystallinity in studied blends.…”
Section: Aliphatic Polyesters/starch Blendssupporting
confidence: 86%
“…Overall, the prepared PLA/PPC blend with 2 phr MA showed optimal performance in mechanical performances. The compatibility between the PLLA and starch (25% amylose content with 11% inherent moisture) has been improved with DCP and MA . The improved compatibility was attributed to the grafting reaction as shown in Figure .…”
Section: Principle and Mechanism Of In Situ Compatibilization Of Polymentioning
confidence: 94%
“…The compatibility between the PLLA and starch (25% amylose content with 11% inherent moisture) has been improved with DCP and MA . The improved compatibility was attributed to the grafting reaction as shown in Figure . The reactive compatibilization of the polymers improved the tensile properties and thermomechanical properties in contrast to the uncompatibilized PLLA/starch blends.…”
Section: Principle and Mechanism Of In Situ Compatibilization Of Polymentioning
confidence: 96%
“…Then, the materials were dried in a vacuum oven at 50°C to evaporate extra diethyl ether in the mixture. All composites were mixed with 50:50 PLLA/starch content according to the previous studies 9,26 as shown in Table II. The mixing process was carried out using an internal mixer (Brabender, Duisburg, Germany) at 180°C for 15 min at 60 rpm.…”
Section: Preparation Of Plla/starch and Treated Rs Compositesmentioning
confidence: 99%